Oxidative Stress in Patients with Rheumatoid Arthritis - Amina Hisham Mohammed; Kassim Salih Abdullah Al Neaimy (College of Nursing,University of Mosul, 2018)
Background: There is a relationship between oxidative stress and rheumatoid arthritis. Objective: To assess oxidative stress parameters represented by total antioxidant status and malondialdehyde, in patients with rheumatoid arthritis. Design: case -control study. Setting: Referred patients from private clinics . Methodology: The study was conducted on patients with rheumatoid arthritis, referred from private clinics of rheumatology. The study period from Nov.1st 2017 and Jun. 1st 2018. Thirty-four female with rheumatoid arthritis, and thirty, sex and age-matched healthy volunteers as control group were participated in the study. Total antioxidants status and malondialdehyde were measured in both groups. Results: Rheumatoid Arthritis patients have lower total antioxidants status values than that of the control group (0.94±0.24 and 1.95±0.20 respectively) (P value <0.0001). The malondialdehyde values was higher in patients group than control group (1.34±0.42 and 0.88±0.26 respectively) (P value <0.0001). Conclusion: Rheumatoid Arthritis patients have decreased level of total antioxidants status and increased level of malondialdehyde than the control group . Key words: Antioxidant status, Oxidative stress, Rheumatoid Arthritis